Energy cooperation between the Republic of China and the European Union - Mara Gubaidullina, Liu Qi, (Opción, 2019)
The study aims to investigate the energy cooperation between the Republic of China and the European Union via comparative quantitative research methods. As a result, the implementation of the initiative "One belt, one road" will further stimulate China’s energy investments in Europe, ensure EU energy security and promote EU energy transformation, as well as development cooperation between the two sides in the field of climate change and promote the integration of the development strategy. In conclusion, China and the EU should make full use of the existing energy platform and play a role in promoting dialogue and exchange.